Proton solvation: competition between acetone and dimethyl sulfoxide - Alexander Lebed; Nikolay Mchedlov-Petrossyan; Dmitriy Filatov; Sergey Goga (Вісник Харківського національного університету: Серія xімія)
This paper presents results of quantum-chemical study of proton exchange equilibrium between acetone (AC) and dimethyl sulfoxide (DMSO). Basing on the previous study of acid-base equilibria in AC with small additives of DMSO, the most probable composition of the lyonium ion is taken as H(DMSO)2+. The equilibrium geometries and energies of solvents molecules and all possible combinations of proton complexes with one or two solvent molecules were calculated in DFT level of theory using B3LYP functional and 6-31G++(d,p) basis set. The energies of solvated proton complexes were then calculated using PCM method. The energy change corresponding to the equilibrium H(AС)2+ + 2 DMSO ⇄ H(DMSO)2+ + 2 AС is –63.1 kJ mol–1 in the gas phase, which is in qualitative agreement with the standard Gibbs energy data, obtained experimentally in the gas phase by Kebarle’s group, –77.6 kJ mol–1, and with ΔGo298 = –49.3 kJ mol–1 for AC solution with small additions of DMSO, determined by the Guss and Kolthoff method.